Characterization of the plant that produces the fruits known in Limón, Costa Rica, as monkey fruits (Artocarpus heterophyllus Lamarck, Moraceae) (Biocenosis, 2024)
The plant Artocarpus heterophyllus (Lamarck, Moraceae), known as monkey fruit in Costa Rica, produces fruits with a strong unpleasant odor when ripe, but its pulp smells like pineapple and banana. Native to southwest India and eastern Malaysia, it is now cultivated in America. Monkey fruit is used to treat various digestive diseases, diabetes, hypertension, among others. It is rich in nutrients such as proteins, fats, carbohydrates, fiber, vitamins, and minerals. The plant is monoecious, with male and female inflorescences appearing on spikes of different types on the same tree. It has varieties with different pulp flavors and is used in various culinary recipes as well as for medicinal purposes.
Keywords: jackfruit; jaca; yaca; nanca; nanjea; panapén; jacktree